Hydrodynamic characteristics and model of fluidized bed reactor with immobilized cells on activated carbon for biohydrogen production - Jamali, Nur Syakina; Md Jahim, Jamaliah; O-Thong, Sompong; Jehlee, Aminee (Elsevier, 2019)
A mathematical model of minimum fluidization velocity (Umf) was developed based on thehydrodynamic characteristics of the fluidized bed reactors (FBR) with immobilised cellsattached to activated carbon at thermophilic biohydrogen fermentation. The maximumhydrogen productivity rate of 7.8 mmolH2/L.h and hydrogen yield of 2.2 molH2/mol of sugarconsumed was obtained when the HRT was shortened from 48 h to 6 h. The presence of theimmobilised cells enriched the biomass composition in the FBR from 4.9 to 7.1 g VSS/L andmaximum energy generated was 58.7 KJ H2/L.d. The FBR had to be operated at a high Umfof0.05e0.44 cm/s and a low terminal velocity of 2.11 cm/s to prevent the immobilised cellsfrom washed out from the FBR, hence achieved an adequate fluidization system. Ascreening of the microbial population by DGGE revealed that theT. thermosaccharolyticumsp. was dominant for all the HRTs, thereby indicating that this bacterium is resilient to-wards environmental disturbances.